2011
DOI: 10.2147/ijn.s25741
|View full text |Cite
|
Sign up to set email alerts
|

Novel mucus-penetrating liposomes as a potential oral drug delivery system: preparation, in vitro characterization, and enhanced cellular uptake

Abstract: Background The aim of this study was to investigate the intestinal mucus-penetrating properties and intestinal cellular uptake of two types of liposomes modified by Pluronic F127 (PF127). Methods The two types of liposomes, ie, PF127-inlaid liposomes and PF127-adsorbed liposomes, were prepared by a thin-film hydration method followed by extrusion, in which coumarin 6 was loaded as a fluorescence marker. A modified Franz diffusion cell mounted with the intestinal mucus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Such surface neutral nanoparticles [9-11, 28] and Pluronic F127 modified liposomes [13, 14] have previously been reported to be muco-inert/mucus penetrating, allowing rapid diffusion through the mucus to the underlying epithelium. Our evaluation of various PEG polymers indicates that phospholipid-PEG conjugates (PE-PEG2K/PE-PEG5K) were more efficient in achieving surface charge neutralization on CRX-601 loaded liposomes compared to Pluronic copolymers (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such surface neutral nanoparticles [9-11, 28] and Pluronic F127 modified liposomes [13, 14] have previously been reported to be muco-inert/mucus penetrating, allowing rapid diffusion through the mucus to the underlying epithelium. Our evaluation of various PEG polymers indicates that phospholipid-PEG conjugates (PE-PEG2K/PE-PEG5K) were more efficient in achieving surface charge neutralization on CRX-601 loaded liposomes compared to Pluronic copolymers (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Such particles, termed mucoinert or mucus penetrating by the authors, were achieved by chemical coupling of low–molecular weight poly(ethylene glycol) (PEG) at high densities on solid nanoparticles [10, 11] or self-assembly of amphiphilic PEG copolymers [12]. Others have described Pluronic F127 coated mucus penetrating liposomes for delivery across the intestinal mucus [13, 14]. However, the effectiveness of mucus penetration, at least for PLGA and polystyrene based systems, has been reported to be highly dependent on the PEG chain length and density [11].…”
Section: Introductionmentioning
confidence: 99%
“…8 Although liposomal systems have been explored for mucosal delivery, 9, 10 there has not been a focus on directly observing the interactions of liposomal formulations with mucus, and how these interactions impact mucosal distribution. Here, we varied the composition of PEG-conjugated lipids to investigate the effect of PEG surface density on liposome mobility in human cervicovaginal mucus (CVM) and vaginal distribution in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the delivered ARV drugs were still present at protective concentrations, 24-hours post-vaginal administration in mice. Previous studies have shown that EPC liposomes have low diffusivity in rat intestinal mucus [43]. We hypothesize that the observed antiviral activity is likely due to entrapment of a small fraction of the administered dose in freshly produced mucus in the mouse genital tract.…”
Section: Discussionmentioning
confidence: 82%